Penerapan Zakat, Infak, Sedekah, dan Wakaf sebagai Strategi Kebijakan Fiskal pada Sharia Microfinance Institution - Latifah, Eny (Indonesian Journal of Islamic Economics and Finance, 2021)
The purpose of this study is to determine the role and function of Zakat, Infak, Sedekah and Waqf as a fiscal policy strategy in the economy of the ummah with the approach of Islamic microfinance institutions. This research method is descriptive qualitative with a case study Approach Whose Data Analysis Uses Data Triangulation.The results showed that zakat, Infak, Sedekah and waqf as fiscal policy strategies are able to develop the economy of the ummah with an approach to financial practices that exist in Islamic microfinance institutions. The provisions for the recipient of ZISWAF funds for personnel or institutions carried out in Islamic Microfinance Institutions are adjusted to the purpose of receiving the funds.